Novel and emerging therapeutics for genetic epilepsies. (2nd November 2021) - Pejčić, Ana; Janković, Slobodan M.; Đešević, Miralem; Gojak, Refet; Lukić, Snežana; Marković, Nenad; Milosavljević, Miloš
ABSTRACT: Introduction: Disease-specific treatments are available only for a minority of patients with genetic epilepsies, while the rest are treated with anticonvulsants, which are ineffective in almost one-third of patients. Areas covered: Recently approved and the most effective emerging therapeutics under development for the treatment of genetic epilepsies are overviewed after systematic search and analysis of relevant literature. Expert opinion: New and emerging drugs for genetic epilepsies exploit one of the two approaches: inhibiting hyperactive brain foci through blocking excitatory or augmenting inhibitory neurotransmission, or correcting the underlying genetic defect. The first is limited by insufficient selectivity of available compounds, and the second by imperfection of currently used vectors of genetic material, unselective and transient transgene expression. Besides, the treatment may come too late, after structural abnormalities and epilepsy deterioration takes place. However, with recent improvements, we can expect to see soon gradual decline in the number of patients with therapy-resistant genetic epilepsies.